Seasonal and Form-Specific Gene Expression Signatures Uncover Different Generational Strategies of the Pelagic Tunicate Salpa thompsoni During the Southern Ocean Winter - Müller, Svenja J.; Michael, Katharina; Urso, Ilenia; Sales, Gabriele; De Pittà, Cristiano; Suberg, Lavinia; Wessels, Wiebke; Pakhomov, Evgeny A.; Meyer, Bettina (Frontiers in Marine Science, 2022)
The pelagic tunicate Salpa thompsoni is recognized as a major metazoan grazer in the Southern Ocean. Long term observations show an increase in this species’ biomass and a southward shift in its distribution both of which are positively correlated with ocean warming and winter sea ice decline around the Antarctic Peninsula. However, our understanding on how salps adapt their life cycle to the extreme seasonality of the Southern Ocean and the putative differences between its two reproductive forms (aggregates, solitaries) is rudimentary. In particular, our current knowledge of whether and how S. thompsoni overwinter is limited, largely due to winter sampling constraints. In this study, we investigated the form-specific gene expression profiles of Salpa thompsoni during the austral autumn and winter. Between the seasons, genes related to translation showed the biggest difference in gene expression. We found more genes were upregulated in solitaries compared to aggregates, indicating a potentially form-specific overwintering strategy. Our data provide first insights into the seasonal and form-specific physiology of salps by considering their complex life cycle, thereby contributing to a more comprehensive understanding of the response of salps to seasonal changes in their environment and to anthropogenic induced global climate change.